Determination of kinetic parameters in laminar flow reactors: II. Experimental aspects - Hanf, Alexander; Volpp, Hans-Robert; Wolfrum, Jürgen (Reactive flows, diffusion and transport, 2007)
In the present contribution laser spectroscopic studies are described in which the chemical kinetics of benchmark elementary reaction steps in different laminar flow reactors were experimentally investigated along with detailed numerical modeling calculations